(3GdLGeY GdUZjQ aj GdfMhs - (3YHO Gddg Hf jhSa Hf CMeO GdCfUGQj GdeUQj GdfMhj , LeGd GdOjf , CHh eMeO, GHf gTGe J (B761 (3g` s
(3ChdgG (B:s
(3GdcdeI bhd eaQO hgj GSe haYd hMQa aGdGSe cdeg JOd Ydi eYfi ai faSgG ZjQ ebQfg HCMO GdCRefI GdKdGKI s
(3BNQgG (B:s
(3hYdi eG GdESJagGejI eLQhQI HMQa hYdi fMh CajOg hde jJSfg Je GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs